Identification of Student Independence and Physics Learning Achievements During COVID-19 Pandemic - Fajar Kurnianto; Anggi Datiatur Rahmat; Heru Kuswanto (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to identify student independence and physics learning achievement during the COVID-19 pandemic. The descriptive qualitative method was used in this study. The research participants are 100 10th-grade students in Vocational High School in Bantul., Yogyakarta. Data collection techniques were carried out using questionnaires and cognitive tests. The results showed that students' independence from others is 55%, self-confidence 60%, self-discipline 48%, sense of responsibility 71%, behavior based on self-initiative 58%, and self-control 63%. Besides, physics learning achievements that have not completed the minimum completeness criteria are complete 63% of those who have reached the minimum completeness criteria are complete 37%. It can be concluded that the independence of students and the results of physics learning achievements during the COVID-19 pandemic is in the medium category.